Custom and Syarak as the Theme in Tambo Minangkabau - Yosi Wulandari; Pujiharto Pujiharto; Sri Ratna Saktimulya (Jurusan Tadris Bahasa Indonesia, 2021)
The aim of the research to describe (1) Sembilan Pucuk laws in Tambo Minangkabau; (2) custom and syarak as the guidelines in Tambo Minangkabau; (3) the command to obey Penghulu based on the custom and syarak. This study concludes that the three theme motifs in Tambo Minangkabau strengthen the role of adat and religion. In Minangkabau, both are present in the history of creating the Minangkabau country, which began with the Nan Nine Pucuk Law as legitimacy. Further, Balai adat (customary hall) and mosques are symbols of harmony between customs and religion in determining the provisions. Indeed, the community leaders, in this case, Penghulu, need to be obeyed because the customs have appointed them based on Qur’an and Hadith (religion).Tujuan penelitian ini adalah untuk mendeskripsikan (1) Undang-Undang Nan sembilan pucuk dalam Tambo Minangkabau; (2) adat dan agama sebagai pedoman dalam Tambo Minangkabau; (3) perintah menaati penghulu berdasarkan adat dan agama. Penelitian ini menyimpulkan bahwa ketiga motif tema dalam Tambo Minangkabau memberikan penguatan peran adat dan agama. Di Minangkabau, keduanya hadir dalam sejarah penciptaan negeri Minangkabau yang diawali dengan adanya Undang-Undang Nan Sembilan Pucuk sebagai legitimasi. Selanjutnya, balai adat dan masjid adalah simbol keharmonisan adat dan agama yang saling berkaitan dalam menentukan keputusan dan ketentuan. Bahkan pemimpin kaum, dalam hal ini penghulu, perlu ditaati perintahnya karena penghulu merupakan pemimpin yang ditetapkan oleh adat dan ditentukan oleh al Quran dan hadis atau agama.